Prevalence of microvascular complications in newly diagnosed type 2 diabetes mellitus in primary healthcare clinics - Wong, Wan Ling; N. Valliappan, Valliammai; Leong, Meng Chue; Aminudin, Siti Noor Azza; Chew, Sarah Ching Jern; Cheong, Ai Theng (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Delayed diagnosis of type 2 diabetes mellitus (T2D) increases the risk of presenting late with microvascular complications due to untreated long-standing hyperglycaemia. This study aimed to determine the prevalence of microvascular complications in newly diagnosed T2D patients in primary healthcare clinics. Methods: This was a cross-sectional study carried out in three government primary healthcare clinics in the state of Selangor, Malaysia. Malaysian aged 18 years and above with newly diagnosed T2D (≤ 6 months of diagnosis) were invited to participate in the study. Data collected included the sociodemographic characteristic and the clinical profile (weight, height, waist circumference, blood pressure, lipid, glycaemic, urine albumin, microalbuminuria and renal profile). The assessment of nephropathy, peripheral neuropathy and retinopathy were performed using standard protocol. Multivariate logistic regression analysis was used to identify the significant factors that contribute to the presence of microvascular complications. Results: A total of 162 newly diagnosed patients were recruited. The majority was women (64%). The mean age was 51 (SD 11) years. About one-third of the patients (27.7%) had developed at least one microvascular complication. Nephropathy was the commonest microvascular complication (19.2%), followed by peripheral neuropathy (8.6%) and retinopathy (6.5%). Poor glycaemic control was found to be a significant factor contributing to the presence of microvascular complications (OR 5.8, 95%CI:1.466, 23.288). Conclusion: There is a high prevalence of microvascular complications among the newly diagnosed T2D. There is a need to develop appropriate strategies to increase the awareness and early detection of T2D.